PERCEPTIONS OF POST-GRADUATE MEDICAL STUDENTS, REGARDING EFFECTIVENESS OF TELEMEDICINE (TM) AS AN INSTRUCTIONAL TOOL: Perceptions of Telemedicine (TM) - Baig, Muhammad Musharaf; Khaliq, Tanwir; Safdar, C. Aqeel (Pakistan Armed Forces Medical Journal, 2014)
Objective: To determine post-graduate medical students’ perceptions regarding effectiveness of telemedicine as an instructional tool. Study Design: It was a pragmatic, sequential mixed method study. Methodology: The data collection was by distribution of questionnaire to groups present both at Holy Family Hospital Rawalpindi and NORI hospital Islamabad. Variables of interest were PERCEPTIONS of medical students and EFFECTIVENESS of telemedicine(TM) as an instructional tool. Ethical committee approval was taken before the study. Results: Out of 384 post-graduate students (PGS), 360 filled the questionnaire performa (response rate 93.75%), age range was 25 to 34 years. Responding to different questions; 95.56% respondents agreed/strongly agreed that TM was a good mode of information transfer (MIT). Another 72.2% respondents understood well the information given through this MIT; 64.4% participants were satisfied with the technical quality of services provided. Some 71.11% preferred TM over lectures and demonstrations, and 85.56% participants agreed/strongly agreed that TM should be accessible to all doctors working in various setups, throughout the country. Responding to the open ended questions; 61.95% participants stated that TM was more effective due to multidisciplinary approach. Regarding the main strengths of TM, 30.83% voted for its multidisciplinary approach and 21% for its interactive nature. Considering the weaknesses of TM 40.83% pointed towards technical problems and 23.89% noted that this MIT lacked face to face exposure Conclusion: The perceptions of overwhelming number of participants were in favor of telemedicine as an instructional tool.